Should Symptoms Be Considered an Indication for Parathyroidectomy in Primary Hyperparathyroidism? - McDow, Alexandria D (Clin Med Insights Endocrinol Diabetes, 2018)
Asymptomatic primary hyperparathyroidism is a very common endocrine condition, yet management of this disease process remains controversial. Primary hyperparathyroidism can lead to a myriad of symptoms which not only decreases the quality of life of patients but also increases the risk of cardiovascular disease, osteoporosis, and kidney stones. Parathyroidectomy is the only known cure for the disease. This review explores the definition of asymptomatic primary hyperparathyroidism, the burden of disease, and the overwhelming benefits of parathyroidectomy.